PENGGUNAAN MEDIA PEMBELAJARAN EDMODO DENGAN DESAIN PEMBELAJARAN ASSURE GUNA MEMPERBAIKI KINERJA GURU PADA MATA PELAJARAN KONSTRUKSI BANGUNAN SISWA KELAS X TEKNIK KONSTRUKSI BATU DAN BETON DI SMK NEGERI 2 SURAKARTA TAHUN PELAJARAN 2016/2017 - Bayu Wicaksono; Roemin toyo; Abdul Haris Setiawan (Universitas Sebelas Maret, 2017)
The current educational process shows that many students who are less active during the learning process. Learning process is focused on the teachers only whichaffects the students’ lack of understanding of the lesson. This study aims todetermine the application of edmodo media with ASSURE learning design on teacher performance and student learning outcomes. This research is a classroom action research conducted in class X TKBB SMK N 2 Surakarta, amounting to 31 students. This research was conducted in two cycles. Each cycle consists of the planning, implementation, observation, and refletion phases. The research instrument used consisted of teacher performance appraisal, student performance appraisal by teacher, cognitive, psychomotor, and affective assessment. The validity of the data using triangulation and analyze the data using descriptive quantitative analyze model by using descriptive statistics.The results showed that at the time of pre-cycle of teacher performance included in category C with value 66,67, cycle I entered in category B with value of 75,00 and cycle II entered in category B with value 83,33. Its mean, Edmodo media with ASSURE learning design can improve teacher performance. In each cycle, as well as the increase in student learning outcomes, this means increased teacher performance also has animpact on increasing student learning outcomesAlexistoto adalah situs hiburan online yang menawarkan akses mudah, beragam permainan, transaksi qris yang praktis, layanan responsif, dan pengalaman bermain game yang nyaman setiap hari.